President's Message - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2004)
Recently, at the Association of periOperative Registered Nurses (AORN) Congress, I had the opportunity to network with the International Federation of Perioperative Nurses (IFPN) Executive and members of the Canadian Council of National Representatives (CNR). It reminded me that there is a great deal of history, and energy, behind all the acronyms.